Gagrak Blitaran: Proses Belajar Kebudayaan di Paguyuban Turonggo Budoyo Mugirejo - Yulinanda, David Bagus; Vivian, Yofi Irvan; Setyoko, Aris (Program Studi Etnomusikologi, Fakultas Ilmu Budaya, Universitas Mulawarman, 2021)
Turonggo Budoyo Mugirejo is a Kuda Lumping group Gagrak Blitaran in the city of Samarinda through the transmigration process. Gagrak Blitaran, on its own, was the identity of this group. The process of learning culture alone played a crucial role in preserving Kuda Lumping Gagrak Blitaran in Samarinda. This study aims to explain the characteristics of Gagrak Blitaran’s music; describe the process of self-study at the Turonggo Budoyo Mugirejo. The study employs qualitative methodologies by applying three phases, some of which define the location of research, data collection techniques, and analysis. Determination of the location aims to focus on the object of research. Data-collection techniques include library studies, informers, interviews, and documentation. The last one is the analysis technique by utilising field data. The study results in accord with the background of the problem and the purpose of the study. Gagrak Blitaran’s music characteristic have been achieved through the four rhythms of sampak, gangsaran, dua-satu (pegon and dangdutan), and satu-satu. The instruments on which these rhythms are based are the kenong, kempul, gong suwukan, and gong ageng. The process of learning its own culture includes internalisation, socialisation and enculturation. The three processes allow each member of the company to have a deeper understanding of Kuda Lumping. It involves a dance technique, beating the Gamelan according to the characteristic of Kuda Lumping Gagrak Blitaran.